A comparative study between routine catheterization and non-catheterization in elective caesarean delivery - Abdullah, Suhaiza (2006)
In the patients who were undergoing elective caesarean section, several preoperative preparation were made such as insertion of Foley's catheter for urinary drainage intra operative and postoperatively. The indication for the regular practice however was of doubtful benefit even though some may think that the procedure facilitates surgery on the lower segment during caesarean section. This routine practice however entails the cost of Foley's catheter and urine bags, urinary symptoms in patients and antibiotic therapy if urine microscopy suggests infection. Objectives: To evaluate role of routine Foley's catheter during and after caesarean section and compare the outcome of routine use of urinary catheterisation and non catheterisation in patient undergoing elective caesarean section. Methods: This study was a case control study conducted from 1st January 2005 until September 2005. All patients who underwent elective caesarean section were included in this study. The patients were divided into 2 groups i.e. control group containing 70 patients who had Foley's catheter inserted preoperatively and were kept during and until day 1 postoperatively and another 70 patients Foley's catheter were not inserted prior to caesarean section but instead the patients were asked to pass urine one hour before start of caesarean section to empty the bladder. The two groups of patients were compared in terms of duration of caesarean section, intra-operative difficulty and also post operative outcome namely time of first void, discomfort at first void, duration of ambulation time postoperatively and incidence of urinary tract infection after caesarean section. Results: In this study, the main ethnic group involved was Malay 93.6o/o followed by Chinese {3.6%), Indian (0. 7%) and Siamese 2.1 %. The commonest indication for elective caesarean section was repeat caesarean section ( 40o/o) followed by breech {19o/o) and placenta praevia (12.4o/o). Regional anaesthesia was given in 82.9°/o of patients while 17.1 o/o were given general anaesthesia. There was no significant difference in terms of duration of caesarean section {46.67 minutes in control versus 44.49 in patients without Foley's catheter in situ), difficulty encountered during performance of caesarean section and mean length of hospital stay after operation (3.1 0 day in control as compared to 3.17 day incase group) .There was however significant difference in discomfort at first void, mean ambulating time and incidence of urinary tract infection in both groups. Conclusion: Continuous urinary catheter by using Foley's catheter is not necessary in patients undergoing elective caesarean section as it does not show any significant difference in terms of mean operating time, difficulty in performing caesarean section but it creates discomfort at first void, delay mean ambulating time and higher risk to urinary tract infection related to CBD.